2005
DOI: 10.1007/s00383-005-1469-7
|View full text |Cite
|
Sign up to set email alerts
|

Focal nodular hyperplasia in a child with Beckwith–Wiedemann syndrome

Abstract: Beckwith-Wiedemann Syndrome (BWS) is associated with somatic overgrowth and a high risk for embryonal tumors, including hepatoblastoma, a highly malignant liver tumor of childhood. Focal nodular hyperplasia (FNH), on the other hand, is a benign tumor of the liver that is uncommon in childhood. Herein we describe a case of FNH in a child with BWS, the first such report in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
1
0
4
Order By: Relevance
“…7 Only 7% of FNH cases are seen in children, and they constitute 2% of pediatric liver tumors. 8 Although a definite etiology of FNH is not clearly known, it has been suggested that it develops as a response of ischemic damage developing related to impairment of hepatic or portal circulation 9 or to thrombosis 10 owing to sickle cell disease in the focal abnormal vascular structures for any reason. Al-Attar et al 1 suggested that abnormal arteriovenous flow could be responsible for FNH development in a patient with hemihypertrophy with vascular malformation in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…7 Only 7% of FNH cases are seen in children, and they constitute 2% of pediatric liver tumors. 8 Although a definite etiology of FNH is not clearly known, it has been suggested that it develops as a response of ischemic damage developing related to impairment of hepatic or portal circulation 9 or to thrombosis 10 owing to sickle cell disease in the focal abnormal vascular structures for any reason. Al-Attar et al 1 suggested that abnormal arteriovenous flow could be responsible for FNH development in a patient with hemihypertrophy with vascular malformation in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Mittels dieser Bildgebung und unter der Voraussetzung, dass bestimmte "key features" (z. B. zentrale Narbe) vorhanden sind, ist die Diagnose radiologisch relativ einfach zu stellen [3,9,21]. Ausnahmen stellen große oder morphologisch nicht eindeutig zuzuordnende Prozesse dar.…”
Section: Diagnose Und Therapieunclassified
“…Mögliche Tumorbiopsien (Feinnadelbiopsie, Stanzbiopsie oder laparoskopische Biopsie entnahme) werden konträr diskutiert, vor allem bei ausgedehnten Raumforderungen aufgrund einer z. T. starken Vaskularisation und dem damit verbundenen Blutungsrisiko [3,9].…”
Section: Diagnose Und Therapieunclassified
See 2 more Smart Citations